Studi Studi Eksperimental dan Kuantitatif Pengaruh Musik Lobi Permainan Terhadap Performa Bermain dan Niat Bermain Siswa: Kasus Kota Batam: Studi Eksperimental dan Kuantitatif Pengaruh Musik Lobi Permainan Terhadap Performa Bermain dan Niat Bermain Siswa: Kasus Kota Batam - Vincent Vincent; Muhammad Ardiansyah (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Music has been widely used in the game development in the form of in-game music, soundtracks and lobby music. As a waiting room for players, musical accompaniment in the game lobby is intended to invite and influence players' moods when playing. The purpose of this study was to collect data related to playing experience to study the relationship of music in the lobby game to the performance and playing intention. This study uses a hybrid method that combines experimental methods with questionnaire methods which are analyzed with the help of statistical applications. The conclusions obtained in this study include that lobby music can cause changes in players' playing performance and also indirectly affect changes in playing intention. This research provides knowledge for game developers about the effective application of music in a game.